Advances in chemistry and biological activity of fluorinated 1,3,5-triazines - Dolzhenko, Anton; Dolzhenko, A.; Chui, W. (Nova Science Publishers, 2007)
The substitution of hydrogen by fluorine as bioisosteric replacement has been practised widely in agricultural and medicinal chemistry. This has led to the discovery of many pesticides and therapeutically useful chemical entities. The 1,3,5-triazine heterocycle is found in many biologically active compounds that exhibit herbicidal, antimicrobial, antiparasitic and anticancer properties. The objective of the chapter is to present a review on the developments in the fields of fluorinated 1,3,5-triazines chemistry and aspects of their application in the last decade.The chapter is organized according to the structural and synthetic aspects of the fluorinated 1,3,5-triazines chemistry. Based on the structure of the heterocyclic nucleus and location of the fluoro substituent, the fluorinated 1,3,5-triazines are presented as three separate groups. Within the first group, 1,3,5-triazines bearing fluorinated substituent at carbon atom of the heterocyclic core are discussed with further structural discrimination by nature of the linkage between 1,3,5-triazine nucleus and the fluorinated substituent. Three types of the connections are categorized namely, C-C bond, C-X bond (X = N, O or S) and 1,3,5-triazines with fluorine atom directly attached to endocyclic carbon atom. Further classification within the subgroups is based on the synthetic methods used for the preparation of fluorinated 1,3,5-triazines.The 1,3,5-triazines bearing fluorinated substituent at nitrogen atom are categorized into a second group, which includes 1,3,5-triazines without substitution at the ring carbon atoms, 1,3,5-triazinones and 1,3,5-triazinium salts. The third group includes the fluorinated fused heterocyclic compounds with 1,3,5-triazine nucleus, particularly azolo-1,3,5-triazines and azino-1,3,5-triazines. Special references are made to specific role of fluorine in the realization of useful chemical and biological properties of the compounds. The practical significance of fluorinated 1,3,5-triazines in organic chemistry and chemical engineering is emphasized. The fluorinated 1,3,5-triazines with interesting pharmacological properties and their synthesis are described, together with the perspectives of the use of fluorinated 1,3,5-triazines as pesticides.